Decomposição fotocatalítica de efluente de celulose e papel - Marques, Rubiane Ganascim (2014)
The pulp and paper industry presents an effluent with a high organic load and high color. Conventional treatments are effective to reduce COD and BOD of the effluent, but even after biological treatment, the effluent is highly colored. Many industries are already using techniques of tertiary wastewater treatment, as ultrafiltration. Another alternative is photocatalysis. The present work aimed to study the photocatalytic degradation of the effluent from an integrated pulp and paper industry after the biological treatment. The catalysts used were: TiO2, Nb2O5, ZnO calcined at 500, 700 and 1000 oC; TiO2 synthesized by sol-gel methodology, suspended and supported on glass beads or NaX zeolite and TiO2, ZnO and Nb2O5 impregnated with iron and silver oxides. The catalysts were characterized by XRD, SEM, photoacoustic spectroscopy, TPD/NH3 and textural analysis. It was found that the calcination temperature changed the surface area of the catalysts, and led to the change of crystalline phase of titanium dioxide when calcined at 1000 °C. The impregnation of Ag2O and Fe2O3 on the catalyst resulted in an increase in surface area in all oxides but not to Ag2O/Nb2O5. Doping with iron and silver oxides also led to a decrease in energy band gap of the catalysts with respect to oxide semiconductors. Preliminary tests to evaluate the influence of radiation and calcination process were carried out in batch reactor and the reaction was accompanied by the reduction of lignin/chlorine-lignin. It was found that the best results were: calcination temperature of 500 °C and radiation of 250 W UV. After the optimization of the calcination conditions and power at the reaction system, the performance of the catalysts with and without impregnation was evaluated under 250W, UV or visible radiation. The performance of the catalysts was evaluated by the reduction of color and COD of the effluent. It was observed that Ag2O/ZnO showed the best activity for COD reduction under visible radiation while, for color, ZnO/UV radiation was the best condition. In other to evaluate the efficiency of the catalysts synthesized by sol-gel methodology, TiO2, TiO2/glass and TiO2/NaX, UV radiation was chosen as this was more effective for commercial titanium dioxide. It was found that the titanium dioxide